2021
DOI: 10.1177/2325958220978113
|View full text |Cite
|
Sign up to set email alerts
|

Autonomy-Supportive Healthcare Climate and HIV-Related Stigma Predict Linkage to HIV Care in Men Who Have Sex With Men in Ghana, West Africa

Abstract: In Ghana, the HIV prevalence among MSM is more than 10 times greater than the general population of adults, and rates of engagement in HIV medical care are low among MSM diagnosed with HIV. Using structured surveys, we investigated the impact of HIV-related stigma, same-sex behavior stigma, and gender nonconformity stigma on linkage to HIV care (LTC) in MSM ( N = 225) living with HIV in Ghana. Autonomy-supportive healthcare climate ( OR = 1.63, p < .01), vicarious HIV stigma ( OR = 2.73, p < .01), and ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 68 publications
1
18
0
Order By: Relevance
“…Multiple HIV HCF stigma-reduction interventions are available [21,22,24,[28][29][30][31][32], and a few studies have developed interventions to address MSM stigma [33][34][35]. However, interventions to address intersectional (HIV, same-sex and gender non-conformity) stigma faced by MSM, particularly in West Africa, are limited [9,23,36].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple HIV HCF stigma-reduction interventions are available [21,22,24,[28][29][30][31][32], and a few studies have developed interventions to address MSM stigma [33][34][35]. However, interventions to address intersectional (HIV, same-sex and gender non-conformity) stigma faced by MSM, particularly in West Africa, are limited [9,23,36].…”
Section: Introductionmentioning
confidence: 99%
“…HCWs and healthcare facilities (HCFs) are essential to HIV prevention, care and treatment. They can also be sources of stigma for both PLHIV and KPs [21,22], who have reported dismissive attitudes, coerced procedures and refusal to deliver treatment [2,6,23,24]. In an HCF study in Ghana, 29% of HCWs indicated that if given the choice, they would prefer not to provide services to MSM [6] .…”
Section: Introductionmentioning
confidence: 99%
“…Interventions must be strengthened to increase the encouragement of HIV-infected women to use contraception in Togo [9]. Although the awareness rate of HIV transmission prevention knowledge and the autonomy of sexual behavior protection among the PLHA population in my country have increased [10], they were affected by the demographic characteristics and related knowledge in different regions [11]. If you had multiple sexual partners for a long time, the proportion of meeting contraceptive needs was not high, which would increase the risk of sexual partners contracting HIV [12].…”
Section: Related Workmentioning
confidence: 98%
“…In a seminal study, MSM in Ghana reported they felt they could not share their sexual identity while seeking care at a health care facility (HCF) and, instead, preferred not to seek care to avoid the discomfort (6). Although the avoidance of HCFs is a protective behavioral strategy used by MSM to avoid exposure to sexual stigma (22), it can have indirect residual impacts on their health through either the lack of detection or delayed detection and treatment of chronic or communicable disease (22,23).…”
Section: Introductionmentioning
confidence: 99%